2014
DOI: 10.15193/zntj/2014/96/021-035
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Factors on Sensory Quality of Pork

Abstract: S u m m a r yThis manuscript presents results of authors` research regarding selected factors influencing sensory pork quality. In the manuscript the role of breed, genes (RYR1 T , RN -, CAST), slaughter weight as well as meatiness is comprised. Additionally, the role of intramuscular fat, ultimate pH and heat treatment on pork quality is discussed. It was stated that the optimization of the sensory aspects of the pork quality should not be limited to one aspect only but it should include the practical use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…For PUL × PLW hybrids fattened for 99 days to a weight of 103.4 kg, Milczarek et al [14] report a fat content in the loin (Longissimus dorsi) of 1.76% and a protein content of 23.70%, while in ham (Adductor) it was 2.11% and 22.81%, respectively, i.e., there was less fat and more protein compared to the values obtained in their own study for this group of hybrids of native breeds. In Poland, it is assumed that the intramuscular fat content required for the optimum taste and flavour of meat should be between 2.5 and 3% [28,29]. In the study presented here, particularly in the meat of pigs of the Puławska breed, the level of intramuscular fat was significantly lower than recommended, which was related to the slaughter weight being too low for this native breed.…”
Section: Proximate Compositionmentioning
confidence: 58%
“…For PUL × PLW hybrids fattened for 99 days to a weight of 103.4 kg, Milczarek et al [14] report a fat content in the loin (Longissimus dorsi) of 1.76% and a protein content of 23.70%, while in ham (Adductor) it was 2.11% and 22.81%, respectively, i.e., there was less fat and more protein compared to the values obtained in their own study for this group of hybrids of native breeds. In Poland, it is assumed that the intramuscular fat content required for the optimum taste and flavour of meat should be between 2.5 and 3% [28,29]. In the study presented here, particularly in the meat of pigs of the Puławska breed, the level of intramuscular fat was significantly lower than recommended, which was related to the slaughter weight being too low for this native breed.…”
Section: Proximate Compositionmentioning
confidence: 58%
“…The results of the current research indicate a slight increase in the pH value of the meat; this was not, however, accompanied by an increase in cooking yield. A significant impact of pH on cooking yield was demonstrated in the studies of Pietrzak et al (2013) and Jaworska and Przybylski (2014). Jakubowska et al (2004) also showed a relationship between pH and efficiency in heat treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The T treatment was characterized by the highest pH ( Table 2 ). It is known that a higher pH increases the juiciness of the meat [ 71 ].…”
Section: Resultsmentioning
confidence: 99%